The Role of Homestays in Shaping the Identity of Tourism Villages: A Case Study in Mekarlaksana Tourism Village - Aries Farhan; Elly Malihah; Rini Andari (Universitas Muhammadiyah Malang, 2024)
Tourism villages can be an alternative in the development of Community Based Tourism (CBT). CBT development in tourist villages is influenced by various aspects, one of which is homestay accommodation. However, there is still limited research related to the identity of tourist villages, especially in the context of homestays. Therefore, this study aims to explore the role played by homestays as a tourist village identity, with a focus on Mekarlaksana Tourism Village. This research used a descriptive qualitative approach, involving a case study in Mekarlaksana Tourism Village. Data were collected through observation and in-depth interviews with Pokdarwsi (Tourism Awareness Group) and homestay managers. In this study determined 10 resource persons with the criteria of people who were born, lived and made a living in the village. The findings of this study reveal that the identity of a tourist village and the role of homestays are key elements in the context of rural tourism. Tourism villages emphasize uniqueness, sustainability, and local wisdom, which include cultural attractions, nature, history, accommodation, and traditions that distinguish the village from other places. The role of homestays in developing the identity of a tourist village has proven to be very important. The findings of this study provide an understanding to tourism village managers that the presence of homestays can attract tourists to visit. Desa wisata dapat menjadi salah satu alternatif dalam pengembangan Community Based Tourism (CBT). Pengembangan CBT di desa wisata dipengaruhi oleh berbagai aspek, salah satunya adalah akomodasi homestay. Namun, masih terbatasnya penelitian terkait identitas desa wisata khususnya dalam konteks homestay. Oleh karena itu, penelitian ini bertujuan untuk mengeksplorasi peran yang dimainkan oleh homestay sebagai identitas desa wisata, dengan fokus pada Desa Wisata Mekarlaksana. Penelitian ini menggunakan pendekatan kualitatif deskriptif, dengan mengambil studi kasus di Desa Wisata Mekarlaksana. Data dikumpulkan melalui observasi dan wawancara mendalam dengan Pokdarwsi (Kelompok Sadar Wisata) dan pengelola homestay. Temuan dari penelitian ini mengungkapkan bahwa identitas desa wisata dan peran homestay merupakan elemen kunci dalam konteks pariwisata pedesaan. Desa wisata menekankan pada keunikan, keberlanjutan, dan kearifan lokal, yang meliputi atraksi budaya, alam, sejarah, akomodasi, dan tradisi yang membedakan desa tersebut dengan tempat lain. Peran homestay dalam mengembangkan identitas desa wisata terbukti sangat penting. Temuan penelitian ini memberikan pemahaman kepada pengelola desa wisata bahwa keberadaan homestay dapat menarik wisatawan untuk berkunjung.